2019
DOI: 10.3390/nu11081896
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk Factors, Microbiota and Parkinson’s Disease: What Is the Current Evidence?

Abstract: Parkinson’s disease (PD) is a frequent neurodegenerative disease among elderly people. Genetic and underlying environmental factors seem to be involved in the pathogenesis of PD related to degeneration of dopaminergic neurons in the striatum. In previous experimental researches oxidative stress, mitochondrial dysfunction, homocysteine, and neuroinflammation have been reported as potential mechanisms. Among environmental factors, nutrition is one of the most investigated areas as it is a potentially modifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 163 publications
1
53
0
4
Order By: Relevance
“…A recent review including prospective studies, nested case-control studies, and meta-analysis to know the relation between diet and PD risk, Boulos et al [ 99 ] found some evidence regarding a potential protective effect of uric acid, polyunsaturated fatty acids, coffee, and tea. In fact, many epidemiological studies indicated tea’s beneficial effect on PD.…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…A recent review including prospective studies, nested case-control studies, and meta-analysis to know the relation between diet and PD risk, Boulos et al [ 99 ] found some evidence regarding a potential protective effect of uric acid, polyunsaturated fatty acids, coffee, and tea. In fact, many epidemiological studies indicated tea’s beneficial effect on PD.…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…Hence, new treatment options for alleviating disease impact remain an unmet need in PD. Environmental factors seem to exert a pivotal role in PD progression and, among them, lifestyle-related factors, such as nutrition, have been widely studied areas due to their potential beneficial roles in the management of PD [ 24 , 25 ]. Natural products are potential candidates for novel adjunctive therapeutic approaches and have gained prominence in the literature, such as ginseng [ 26 , 27 ], curcumin [ 28 , 29 ], cannabidiol [ 30 , 31 ], green/black tea [ 32 , 33 ], and coffee [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in contrast to milk intake, increased serum uric acid levels, coffee and green tea consumption and smoking reduce the risk of PD [ 95 , 96 ]. Recent evidence underlines that urate, caffeine, green tea polyphenols and nicotine all promote autophagy.…”
Section: Milk: a Signaling System For Postnatal Growth And Differementioning
confidence: 99%